Effects of dietary fibre type on blood pressure: a systematic review and meta-analysis of randomized controlled trials of healthy individuals. Issue 5 (May 2015) - Evans, Charlotte E.L.; Greenwood, Darren C.; Threapleton, Diane E.; Cleghorn, Christine L.; Nykjaer, Camilla; Woodhead, Charlotte E.; Gale, Christopher P.; Burley, Victoria J.
Abstract : Objective: To determine the effect of different types of dietary fibre on SBP and DBP. Methods: A systematic review of the literature and a meta-analysis of randomized controlled trials using random-effects models. Eligibility criteria for studies included randomized controlled trials of at least 6 weeks duration, testing a fibre isolate or fibre-rich diet against a control or placebo published between 1 January 1990 and 1 December 2013. Results: Twenty-eight trials met the inclusion criteria and reported fibre intake and SBP and/or DBP. Eighteen trials were included in a meta-analysis. Studies were categorized into 1 of 12 fibre-type categories. The pooled estimates for all fibre types were −0.9 mmHg [95% confidence interval (CI) −2.5 to 0.6 mmHg] and −0.7 mmHg (95% CI −1.9 to 0.5 mmHg) for SBP and DBP, respectively. The median difference in total fibre was 6 g. Analyses of specific fibre types concluded that diets rich in beta-glucans reduce SBP by 2.9 mmHg (95% CI 0.9 to 4.9 mmHg) and DBP by 1.5 mmHg (95% CI 0.2 to 2.7 mmHg) for a median difference in beta-glucans of 4 g. Heterogeneity for individual fibre types was generally low. Conclusions: Higher consumption of beta-glucan fibre is associated with lower SBP and DBP. The results of this review are consistent with recommendations to increase consumption of foods rich in dietary fibre, but some additional emphasis on sources of beta-glucans, such as oats and barley, may be warranted. Abstract : Supplemental Digital Content is available in the text